A diagnostic dilemma in a case of pulmonary inflammatory myofibroblastic tumour. (18th April 2016) - Asciak, Rachelle; Gouder, Caroline; Bilocca, David; Montefort, Stephen
Abstract : An 18-year-old man presented to the local hospital in Malta, with dyspnoea, cough, mild haemoptysis, chest pain and night sweats. CT revealed a right hilar mass. Pleural tap, bronchoscopy and open lung biopsy were inconclusive. Biopsies obtained at repeat bronchoscopy and endobronchial ultrasound (EBUS) revealed a likely diagnosis of inflammatory myofibroblastic tumour (IMT). The patient subsequently underwent right pneumonectomy, and histology revealed the presence of two further nodules apart from the main tumour. Follow-up with positron emission tomography (PET)/CT showed the development of a right basal paracardial lesion due to recurrence and the presence of lymph node, pleural and skeletal disease. Despite radiotherapy to the recurrent nodule and chemotherapy, there was skeletal disease progression. Treatment with an anaplastic lymphoma kinase inhibitor, ceritinib, resulted in very good metabolic response. This case report highlights the importance of keeping IMT in mind when the diagnosis of lung tumours is difficult, as delayed diagnosis may lead to worsened prognosis.